How to define the wildland-urban interface? Methods and limitations: towards a unified protocol - Gonzalez, Sofía; Ghermandi, Luciana (Frontiers in Environmental Science, 2024)
In recent decades, the risk of Wildland-Urban Interface (WUI) fires has increased due to urban growth, particularly in regions with a Mediterranean climate. The identification of the WUI is crucial for formulating fire prevention and management measures. However, there is no unified methodology for defining the WUI and it is not clear if proposals that emerge from scientific research are implemented by fire management agencies. Our objectives were to identify, describe, and compare the methods and criteria used by land and fire management agencies to define the WUI in Mediterranean-climate countries.We conducted a review of laws and fire prevention and management plans and protocols on official websites of administrative bodies and agencies of the USA, Spain,